2017
DOI: 10.18632/oncotarget.19541
|View full text |Cite
|
Sign up to set email alerts
|

miR-223 promotes colon cancer by directly targeting p120 catenin

Abstract: microRNA (miRNA) dysregulation is frequently observed in colon cancer. Previous studies found that miR-223 is upregulated in colon cancer and functions as an oncogene. Conversely, p120 is often downregulated or even absent in colon cancer, and is a likely tumor suppressor. The present study showed that increased miR-223 and decreased p120 levels are associated with colon cancer malignancy, and p120 expression is negatively correlated with miR-223 expression. A dual luciferase reporter assay showed that miR-223… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…highlightedmiR-223 as a tumor inhibitor in breast cancer [14], Eto et al have reportedmiR-223 inhibits gastric cancer progression [15], and Dong et al have shown that miR-223 is used to control the increase of cell death rate to control the increase of liver cancer cells [18]. Furthermore, several researches have found that miR-223 repression colon cancer progression [19][20][21].In the latest research, we observed decreased act of miR-223 in 38 paired PTC tissue specimens. We also studied the relationship between miR-223 and clinical pathological parameters of PTC, and found that there is a certain relationship between lower miR-223 level and late TNM stage and cervical metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…highlightedmiR-223 as a tumor inhibitor in breast cancer [14], Eto et al have reportedmiR-223 inhibits gastric cancer progression [15], and Dong et al have shown that miR-223 is used to control the increase of cell death rate to control the increase of liver cancer cells [18]. Furthermore, several researches have found that miR-223 repression colon cancer progression [19][20][21].In the latest research, we observed decreased act of miR-223 in 38 paired PTC tissue specimens. We also studied the relationship between miR-223 and clinical pathological parameters of PTC, and found that there is a certain relationship between lower miR-223 level and late TNM stage and cervical metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-223 phenotypes have been reported in both hematological malignancies [8][9][10][11][12] and in solid tumors, such as breast cancer [13,14], gastric cancer [15,16], hepatic cancer [17,18], and colon cancer [19][20][21]. However, what kind of function does miR-223 have in PTC?…”
Section: Introductionmentioning
confidence: 99%
“…Also, Liu et al showed miR‐223 expression was remarkably increased in colon cancer tissues and inversely correlated with p120 expression. miR‐223 overexpression increased c‐Myc, cyclinD1, MMP7 protein levels which are related to cell proliferation and invasion, suggesting miR‐223 played an oncogenic role in colon cancer . In non‐small cell lung cancer (NSCLC), high miR‐223 expression was observed in sputum or blood samples of NSCLC patients, and ROC curve analysis revealed serum miR‐223 had high predictive accuracy in early‐stage NSCLC detection .…”
Section: Discussionmentioning
confidence: 99%
“…miR-223 overexpression increased c-Myc, cyclinD1, MMP7 protein levels which are related to cell proliferation and invasion, suggesting miR-223 played an oncogenic role in colon cancer. 29 In non-small cell lung cancer (NSCLC), high miR-223 expression was observed in sputum or blood samples of NSCLC patients, and ROC curve analysis revealed serum miR-223 had high predictive accuracy in early-stage NSCLC detection. 30,31 The role of miR-223 in human tumorigenesis seemed to be a doubleedged sword and its function might depend on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, such as the United States, about 50 000 deaths appeared every year . Due to recurrence and localized or distant metastases, most patients with colorectal cancer had very poor prognosis and short survival time . At present, many progresses have been made in screening tests and targeted therapeutics for colorectal cancer, which was helpful to reduce mortality.…”
Section: Introductionmentioning
confidence: 99%